2001
DOI: 10.1007/bf02438646
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal evidence for precision gripping inCebus apella

Abstract: Skeletal evidence for precision gripping in Cebus apellaWe compared the thumb morphology of Cebus apella to that of several other primate species in order to determine whether robust thumbs are associated with tool-use. We found that thumb robusticity was greater for Cebus apella than for all other represented nonhuman species except Gorilla gorilla. Further, thumb robusticity in Cebus apella was similar to that of Australopithecus afarensis but lesser than that of other represented hominids, including modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Macaques presumably have more hand control than capuchins because they have greater volar opposability, have better individual digit control, and have a saddle joints in their thumb [Christel & Fragaszy, 2000;Fragaszy, 1998] and therefore we might expect macaques to be able to exert more control and force in a precision grip than capuchins. Despite this difference, capuchins are highly manipulative, have an exceptional degree of innervation between the spine and fingers [Fragaszy, 1998], and have greater thumb robusticity than macaques [Westergaard & Kuhn, 2001]. These factors can account for the convergence we see in the hand dexterity of macaques and capuchins, despite their differences in hand anatomy.…”
Section: A Three-species Model For Nhp Stone Tool Usementioning
confidence: 99%
“…Macaques presumably have more hand control than capuchins because they have greater volar opposability, have better individual digit control, and have a saddle joints in their thumb [Christel & Fragaszy, 2000;Fragaszy, 1998] and therefore we might expect macaques to be able to exert more control and force in a precision grip than capuchins. Despite this difference, capuchins are highly manipulative, have an exceptional degree of innervation between the spine and fingers [Fragaszy, 1998], and have greater thumb robusticity than macaques [Westergaard & Kuhn, 2001]. These factors can account for the convergence we see in the hand dexterity of macaques and capuchins, despite their differences in hand anatomy.…”
Section: A Three-species Model For Nhp Stone Tool Usementioning
confidence: 99%
“…We argued previously that morphological convergences between Cebus and the great apes evolved as adaptations for extractive foraging, and that these morphological characters (such as increased neocortical development, large brains relative to body size, highly mobile thumbs, and thumb robusticity [e.g. Westergaard, 1998;Westergaard & Kuhn, 2001]) facilitated behaviors such as tool use and accurate throwing.…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, we examined aimed-throwing behavior in tufted capuchin monkeys (Cebus apella). Capuchins are highly manipulative, sexually dimorphic, omnivorous New World monkeys that display a suite of morphological and behavioral convergences with the hominoids, including an allometric brain to body weight relationship similar to that of Pan, increased neocortical development, and a highly mobile thumb [Costello & Fragaszy, 1988;Fragaszy & Mitchell, 1990;Westergaard & Kuhn, 2001]. Given the known cognitive and manipulative capabilities of capuchins, as well as their phylogenetic distance from great apes and humans, we previously suggested that capuchins, as a model of early hominid behavior, represent a unique opportunity to gain insight into the social and ecological (rather than genetic) selective pressures that result in similar behavioral and morphological convergences among Cebus, Pan, and Homo [Westergaard, 1998].…”
Section: Introductionmentioning
confidence: 99%